2020
DOI: 10.17219/acem/111377
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 decline and lipid peroxidation rise reflect a degree of brain atrophy and vascular impairment in dementia

Abstract: Bednarz-Misa I, Berdowska I, Zboch M, et al. Paraoxonase 1 decline and lipid peroxidation rise reflect a degree of brain atrophy and vascular impairment in dementia. AbstractBackground. Paraoxonase 1 (PON1) is an enzyme with the capability to protect against lipid oxidation and atherosclerotic lesions formation. Impaired antioxidative capacity and enhanced lipid peroxidation (reflected by malondialdehyde rise) accompany dementias.Objectives. The aim of this study was to discern the possible differences in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
(51 reference statements)
0
11
0
1
Order By: Relevance
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation 28‐31 . Therefore, obesity is not only characterized by an OS state, but it is also defined as a low‐grade inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation 28‐31 . Therefore, obesity is not only characterized by an OS state, but it is also defined as a low‐grade inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have concluded that the principal biochemical mechanisms involved in inducing OS in obesity are hyperleptinaemia, low antioxidant defences and chronic inflammation. [28][29][30][31] Therefore, obesity is not only characterized by an OS state, but it is also defined as a low-grade inflammatory disease. In agreement with this, together with the low values of the antioxidant enzymes PON1 and CAT, we found leptin values 4 times higher in morbidly obese patients than 1 year after BS, in addition to high CRP levels that were 5 times higher before BS.…”
Section: F I G U R Ementioning
confidence: 99%
“…Disulfide (µmol / l) / alb (g / l). Oxidative stress index = total oxidant status / total antioxidant status) [19][20][21][22][23][24][25][26][27]. The results of hemogram and Vitamin B12, 25 OH D levels were retrospectively taken from their files.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The activity calculation was made by subtracting the basal PON1 activity from the stimulated PON1 activity. The results are given in U / l [10].…”
Section: Paraoxonase 1 (Pon1)mentioning
confidence: 99%